Jones v. Gerhardstein: the involuntarily committed mental patient's right to refuse treatment with psychotropic drugs - Ledwith, D M J (Wisconsin law review, 1990)
The question of whether an involuntary committed mental patient has a fundamental right to refuse treatment with psychotropic drugs continues to be a subject of much debate. Over the past twenty-five years, psychotropic drugs have become the most common form of treatment for the mentally ill. For many patients, these drugs provide substantial benefits; for others, however, they produce severe, sometimes debilitating, side effects. Because of the possibility of serious harm to the patient and because of the potential for abuse of drug treatment by psychiatric staffs, the mental health bar generally has argued for increased procedural protection for mental patients. In Jones v. Gerhardstein, the Wisconsin Supreme Court responded to these concerns by requiring that a judicial hearing be held on the issue of a patient's competency to refuse treatment before the attending physician may administer medication without the patient's consent. This Note discusses the controversy between the legal and medical communities over treatment refusal by mentally ill patients in light of the impact of the Jones decision on institutional practice and on refusing patients. The author argues that the strictly rights-based analysis used by the Jones court has done little to benefit involuntarily committed mental patients. The author suggests alternative ways of approaching treatment refusal that might be more responsive to the distinctive needs of the mentally ill.